Number and distribution of nevi at the age of ten in 244 schoolchildren. - Troccoli, T.; Mazzotta, F.; Tarantino, G.; Ciampo, L.; Berloco, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2000)
The number and distribution of melanocytic nevi at the age of ten were investigated in 244 students. The latter were chosen at random in 15 classes of the primary school of Bari (Italy). Besides the age and sex, in these subjects were investigated the presence of ephelides, nonmelanocytic nevi, the total number of melanocytic nevi, the number of such lesions for each site -head, trunk, upper and lower limbs- and the site of the largest nevus. Ephelides were found in 49 subjects (19%). Among the nonmelanocytic nevi, hyperpigmented nevus was the most frequent (19 cases -8%-). 66% of students showed a total number of melanocytic nevi higher than 10. This percentage was 72 in subjects with ephelides. The highest concentration of melanocytic nevi was on the head, whereas the lowest was on the lower limbs. No difference was shown between sexes with regard to the number and distribution of melanocytic nevi.